Fawn survival, cause-specific mortality, and bed-site selection of white-tailed deer and mule deer in Western Kansas - Kern, Mitchell J. (Kansas State University, 2019)
Mule deer (Odocoileus hemionus) and white-tailed deer (O. virginianus) are common sympatric deer species in the Great Plains and western United States that have exhibited divergent population trends temporally and spatially. Mule deer populations are declining and contracting to the west while white-tailed deer populations are expanding. Species-specific differences in fawn recruitment is one proposed explanation for these observed trends, although the underlying causes remain unknown. To determine if landscape or other habitat changes are affecting the two deer species in different ways, we studied bed-site selection of mule deer and white-tailed deer fawns in western Kansas at microhabitat and landscape scales. We also assessed how fawn intrinsic factors, doe maternal condition, and bed-site habitat characteristics influenced survival of mule deer and white-tailed deer fawns. In February 2018 and 2019, we captured 120 adult does (60 mule deer, 60 white-tailed deer) using helicopter net-gun techniques and deployed 120 vaginal implant transmitters (VITs) synchronized with GPS collars deployed on does. Upon VIT expulsion, a birthing event notification was triggered, which narrowed search efforts for fawns. We captured and radio-collared 100 fawns (53 mule deer, 47 white-tailed deer) during 12 May- 23 June in 2018 and 2019. Fawns were visually located daily using ground-based radio-telemetry and we assessed bed-site selection, cause-specific mortality, and survival rates until fawns reached 10 weeks of age. Overall, fawn survival was low (0.32 ± 0.06) and did not differ between species (mule deer: 0.25 ± 0.08; white-tailed deer: 0.41 ± 0.08). Adult chest girth was positively associated with 70-day white-tailed deer fawn survival, longer fawn body length increased 7-day white-tailed deer fawn survival, and fawn sex best predicted 7-day mule deer fawn survival. Model uncertainty indicated fawn intrinsic factors and maternal conditions may be poor predictors of fawn survival. White-tailed deer survival was lower for fawns with more woodland in their home ranges and mule deer fawn survival exhibited a positive quadratic relationship with the amount of grassland within the home range. Mule deer fawn survival increased with the amount of edge and disaggregation within a home range, but landscape configuration did not explain survival of white-tailed deer fawns. We analyzed microhabitat characteristics at 2689 fawn bed-sites and 2689 paired random points. Bed-site selection differed by species; however, vegetative structure was the most influential microhabitat characteristic for both deer species. Mule deer fawns selected for 75% visual obstruction 8.4 dm tall, less grass cover, more succulent cover, and 56% shrub cover at bed-sites. White-tailed deer fawns selected for 25% visual obstruction 9.2 dm tall, 71% forest canopy cover, and less grass cover and bare-ground at bed-sites. The two species also showed differences in landscape selection. The odds of a white-tailed deer fawn bed-site increased 5.88 times in woodlands, whereas odds of a mule deer fawn bed-site increased 2.85 times in CRP. Our research suggests white-tailed deer fawns and mule deer fawns selected different characteristics for bed-sites at the microhabitat and landscape scale. Bed-site selection likely influences fawn survival, which could affect fawn recruitment. Managers should focus on maintaining heterogeneous landscapes composed mainly of native and Conservation Reserve Program grasslands with abundant cover to enhance mule deer fawn survival and bolster adult populations.
Keywords: Fawn; Survival; White-tailed deer; Mule deer; Deer